Synthesis and Crystal Structure of a Mononuclear Copper(II) Complex - Zhang, Hong-Ge (Asian Journal of Chemistry, 2013)
A new mononuclear complex with the Schiff base ligand 2-[(2-bromo-phenylimino)-methyl]-4-chloro-phenol (HL), namely CuL2, has been synthesized and characterized by X-ray singlecrystal diffraction analysis. The complex crystallizes in monoclinic system, space group P21/c with a = 9.568(2) Å, b = 10.853(3) Å, c = 12.047(3) Å, b = 105.965(7)º, V = 1202.8(6) Å3, Mr = 682.67, Dc = 1.885 Mg/m3, Z = 2, μ = 4.481 mm-1, F(000) = 670, R = 0.0450 and wR2 = 0.1225. The coordination geometry in the copper(II) complex is slightly distorted tetrahedral and the unit CuL2 is linked into a three-dimensional network structure by weak halogen… halogen and C-H···p interactions and the conformation and packing is also stabilized by them.